2022
DOI: 10.1093/ejo/cjab080
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of two types of fixed maxillary retainers and a removable vacuum-formed maxillary retainer: a randomized controlled trial

Abstract: Summary Background There has been an increased interest in conducting healthcare economic evaluations. Also, orthodontic treatments have gathered focus from an economic point of view, however orthodontic research seldom examines both clinical and economic outcomes. Objective To evaluate and compare the costs of three retention methods: a bonded retainer to the maxillary four incisors, a bonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The authors reported no difference in retention cost or treatment time cost. However, they also reported that it was statistically significantly more expensive to repair the vacuum-formed retainers in terms of material and emergency cost (Sonesson et al, 2022). This outcome may be particularly interesting to readers who assumed that bonded retainers were always associated with a higher cost.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported no difference in retention cost or treatment time cost. However, they also reported that it was statistically significantly more expensive to repair the vacuum-formed retainers in terms of material and emergency cost (Sonesson et al, 2022). This outcome may be particularly interesting to readers who assumed that bonded retainers were always associated with a higher cost.…”
Section: Introductionmentioning
confidence: 99%
“…These types of removable appliances have other advantages such as comfort, reduction in chairside time, possibility of removing them both during meals and for the brushing of teeth such as clear aligners [ 5 ]. Despite these pros, costs are higher for vacuum-formed retainers [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%